Parental Attitudes toward Schooling in Low-Income Households: A Qualitative Study from Dhading, Nepal - Bista , Shreesha (Solukhumbu Multiple Campus Research Journal, 2025)
Article 26 of the Universal Declaration of Human Rights (1948) mentions that every person has the right to education. It states that all elementary education shall be compulsory for the overall development of human personality and to strengthen human rights, and has given parents the right to choose the kind of education for children. Yet, rural and low-income communities in Nepal still face significant barriers to education, and those barriers often mar parents’ decisions to provide education to their children. This qualitative study examines the attitude of parents towards education in low-income households of Bhumesthan VDC of Dhading district. I have taken a narrative inquiry approach within an interpretivist framework to explore how parents frame their decisions on providing education to their children in relation to economic constraints, traditional gender norms, and systemic challenges. Findings of this study reveal that there is a complex interplay between aspiration towards education and actual constraints faced- On the one hand, parents value education as a potential route to better livelihood, on the other hand, immediate demands towards economic contributions including support to subsistence agriculture, cultural expectations regarding gender norms, and geographical barriers such as long distance travel temper their decision to provide quality education to their children. I have identified “aspirations vs. pragmatism” as a key theme in this study, which refers to the balance that parents create between their hope for their children’s futures and the realities of daily survival. Based on the findings of this study, I recommend context-specific interventions to provide access to education, rather than relying on generic, country-wide policy. One way to do that could be by aligning school calendars with agricultural cycles (which is done in many districts), expanding flexible learning opportunities through infrastructural support to children, and strengthening school–community partnerships. This study centers on the voices of parents from low-income households and offers a human-centered approach towards discussion related to providing access to education.